Bicyclic Derivatives of L‐Idonojirimycin as Pharmacological Chaperones for Neuronopathic Forms of Gaucher Disease. Issue 8 (18th April 2013) - Alfonso, Pilar; Andreu, Vanesa; Pino‐Angeles, Almudena; Moya‐García, Aurelio A.; García‐Moreno, M. Isabel; Rodríguez‐Rey, José C.; Sánchez‐Jiménez, Francisca; Pocoví, Miguel; Ortiz Mellet, Carmen; García Fernández, Jose M.; Giraldo, Pilar
<x xml:space="preserve">Abstract</x> New human β‐glucocerebrosidase (GCase) ligands with rigid 1, 6‐anhydro‐β‐L‐idonojirimycin cores have been designed with the aid of molecular modeling. Efficient pharmacological chaperones for the L444P (trafficking‐incompetent) mutant GCase enzyme associated with type 2 and 3 Gaucher disease (GD) were identified.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>